2023
DOI: 10.1111/jcmm.17895
|View full text |Cite
|
Sign up to set email alerts
|

Radiological assessment of immunotherapy effects and immune checkpoint‐related pneumonitis for lung cancer

Abstract: Immune checkpoint inhibitors (ICIs) therapy have revolutionized advanced lung cancer care. Interestingly, the host responses for patients received ICIs therapy are distinguishing from those with cytotoxic drugs, showing potential initial transient worsening of disease burden, pseudoprogression and delayed time to treatment response. Thus, a new imaging criterion to evaluate the response for immunotherapy should be developed. ICIs treatment is associated with unique adverse events, including potential life‐thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 99 publications
(268 reference statements)
0
1
0
Order By: Relevance
“…Meanwhile, REC inhibiting PD-1 and PD-L1 can exacerbate this response. In this study, the incidence of radiation pneumonitis in the experimental and control groups were 31.91% and 25.89%, respectively, with the experimental group showing a 23.25% increase compared to the control group (38,(56)(57)(58). A study by Tong etal (59) found that the combination of chemoradiotherapy and PD-1/PD-L1 inhibitors increased the i n c i d e n c e o f p n e u m o n i t i s b y 2 5 .…”
Section: Discussionmentioning
confidence: 58%
“…Meanwhile, REC inhibiting PD-1 and PD-L1 can exacerbate this response. In this study, the incidence of radiation pneumonitis in the experimental and control groups were 31.91% and 25.89%, respectively, with the experimental group showing a 23.25% increase compared to the control group (38,(56)(57)(58). A study by Tong etal (59) found that the combination of chemoradiotherapy and PD-1/PD-L1 inhibitors increased the i n c i d e n c e o f p n e u m o n i t i s b y 2 5 .…”
Section: Discussionmentioning
confidence: 58%